2002
DOI: 10.1074/jbc.m202449200
|View full text |Cite
|
Sign up to set email alerts
|

WY14,643, a Peroxisome Proliferator-activated Receptor α (PPARα) Agonist, Improves Hepatic and Muscle Steatosis and Reverses Insulin Resistance in Lipoatrophic A-ZIP/F-1 Mice

Abstract: WY14,643 is a specific peroxisome proliferator-activated receptor ␣ (PPAR␣) agonist with strong hypolipidemic effects. Here we have examined the effect of WY14,643 in the A-ZIP/F-1 mouse, a model of severe lipoatrophic diabetes. With 1 week of treatment, all doses of WY14,643 that were tested normalized serum triglyceride and fatty acid levels. Glucose and insulin levels also improved but only with high doses and longer treatment duration. WY14,643 reduced liver and muscle triglyceride content and increased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
132
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(146 citation statements)
references
References 33 publications
(43 reference statements)
8
132
4
1
Order By: Relevance
“…Studies in animals indicate that PPAR-α agonists increase hepatic fat oxidation and reduce hepatic fat content in association with enhanced insulin-mediated suppression of EGP [3,7,43,48]. Although hepatic fat oxidation was not measured in the present study, we did not observe a significant reduction in hepatic fat content or an increase in hepatic insulin sensitivity (in contrast to PIO therapy) following FENO therapy.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Studies in animals indicate that PPAR-α agonists increase hepatic fat oxidation and reduce hepatic fat content in association with enhanced insulin-mediated suppression of EGP [3,7,43,48]. Although hepatic fat oxidation was not measured in the present study, we did not observe a significant reduction in hepatic fat content or an increase in hepatic insulin sensitivity (in contrast to PIO therapy) following FENO therapy.…”
Section: Discussioncontrasting
confidence: 82%
“…Studies in rodents conclusively demonstrate that PPAR-α activation with FENO and other more potent PPAR-α agents enhances peripheral (muscle) and hepatic insulin sensitivity [4][5][6][7][8]. Although PPAR-α-null mice do not manifest any obvious alteration in insulin sensitivity [42], PPAR-α activation in nutritional (high-fat diet), genetic (Zucker obese fa/fa rat), and lipoatrophic (A-ZIP/ F-1) models of insulin resistance markedly improves insulin sensitivity [4,7,43] and reduces visceral fat in the two former models. Intracellular fatty acids and their derivatives interfere with insulin-stimulated glucose metabolism, through an effect on the insulin-signalling pathway, possibly by activating protein kinase C [1,44].…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have shown in rats fed a high-fat, 29 highfructose, 30 or choline-deficient diet, 31 and in the A-ZIP/ F-1 mouse, 32 that administration of a PPAR␣ agonist reduces or prevents the development of hepatic steatosis. Although rats fed a choline-deficient diet may develop a mild form of steatohepatitis, 31,33 the present study shows that a PPAR␣ agonist can prevent steatohepatitis in a model characterized by moderate inflammatory changes, hepatocellular degeneration, and ultimately progressive pericellular fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ␤-oxidation is often associated with increased insulin sensitivity (40,41). In the plin Ϫ/Ϫ mice, there is increased ␤-oxidation but no major change in insulin sensitivity when the animals are young.…”
Section: Fig 4 Intraperitoneal Insulin Tolerance Test In Plinmentioning
confidence: 99%